Refugee Status Determination in South Africa: A systematic literature review - Moyanga, Robin (Department of Information Systems, 2024)
The South African Department of Home Affairs is tasked with being the custodians to the country's borders and providing asylum seekers and refugees with the required legalizing documentation in accordance with the Refugees Act of 1998. However, overtime newer and more stringent immigration policy, pervasive maladministration, and corruption have all contributed to an increase in clandestine migration into the country. These highlighted issues faced in the Refugee Status Determination Process have long been associated with the inadequacies of existing legacy systems, poor processes control, and a lack accountability. Illegal undocumented immigrants living in South Africa today are unable to access their basic constitutional rights due to their unrecognized legal status in the country. Blockchain Technology has the potential to resolve some of these Refugee Status Determination administrative challenges by fully digitizing and streamlining the application process for undocumented migrants, by leveraging distributed ledger technology as a means of establishing a transparent, fair, and efficient application process. A precedent for the adoption of Blockchain-enabled solutions for facilitating public administrative procedures has already been established, with several countries around the world already having implemented Blockchainenabled immigration control management solutions. However, the indifference and/or hesitancy of the South African Department of Home Affairs towards Blockchain technology adoption highlights the presence of unspecified institutional barriers to adoption which need to be fully understood. This Systematic Literature Review will critically analyse, appraise, and synthesize the prevailing research on factors affecting Blockchain adoption to construct new knowledge from the existing literature. This literature review utilises the TechnologyOrganization-Environment theoretical framework as the theoretical basis to help identify and classify the institutional factors affecting Blockchain adoption at an institution-level.